2020
DOI: 10.1016/j.physd.2020.132485
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional patterns in dip coating - first steps on the continuation path

Abstract: We present a brief comparative investigation of the bifurcation structure related to the formation of two-dimensional deposition patterns as described by continuum models of Cahn-Hilliard type. These are, on the one hand a driven Cahn-Hilliard model for Langmuir-Blodgett transfer of a surfactant layer from the surface of a bath onto a moving plate and on the other hand a driven thin-film equation modelling the surface acoustic wave-driven coating of a plate by a simple liquid. In both cases, we present selecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Additionally, it has been found that SDS has a strong influence on the formation of SiO 2 spherical films at different concentrations [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been found that SDS has a strong influence on the formation of SiO 2 spherical films at different concentrations [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…with the positive mobility function M g [648][649][650][651][652]. If a c is a vector containing multiple variables, M g is a matrix that is positive definite [546,648,653].…”
Section: Nonequilibrium Thermodynamicsmentioning
confidence: 99%
“…Under proper conditions, coating solutions of all types of materials could be easily deposited on a substrate, including biomolecules, polymers, nanoparticles, nanocomposites, and carbon materials. Note that this seemingly simple process involves complicated chemical and physical science. Through mastering the composition of solutions, the withdrawal speed, and all the evaporation-related parameters, it is found that dip-coating has a high degree of control on the morphology and structure of depositions, such as regular line patterns, interconnected stripes, ladder structures, and branched structures. However, the systematic report of the transitions between various different patterns are still rare.…”
Section: Introductionmentioning
confidence: 99%